American Law Institute Releases a Volume of the Restatement Fourth of the Foreign Relations Law of the United States, Partially Revising the Restatement Third. Issue 2 (9th April 2019) - Unknown
Abstract : In late 2018, the American Law Institute released a volume of the Restatement Fourth of the Foreign Relations Law of the United States. Initiated in October 2012 under the direction of Coordinating Reporters Sarah Cleveland and Paul Stephan, this volume covers three areas of U.S. foreign relations law: treaties, jurisdiction, and sovereign immunity. It remains to be seen whether the American Law Institute will revisit other portions of the Restatement Third, which was published in 1987. "[I]n the meantime, the provisions of the Third Restatement remain the position of The American Law Institute except where superseded by provisions in this Fourth Restatement."